2017
DOI: 10.5812/ircmj.58673
|View full text |Cite
|
Sign up to set email alerts
|

Normative and Subjective Oral Health Evaluation among Smoker and non-Smoker Adolescents of Qazvin, Iran, in 2015

Abstract: Background: Smoking among adolescents is a universal matter. Several findings suggest that smoking can lead to impaired oral health. Objectives: The current study was undertaken to evaluate the normative and subjective oral health status of 13-year-old smokers and nonsmokers in Qazvin, Iran. Methods: This cross-sectional study was carried out on a multistage cluster sample of 519 adolescents in Qazvin, Iran, in 2015. A self-administered questionnaire comprising three parts pertaining to oral health behavior (f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“… Reference Country Study design Study participants Smoking definition Diagnosis of halitosis Subgroup (halitosis, YES/NO) Smokers Nonsmokers OR Patient group (n) (n) (95% CI) Al Ansari et al [31] Kuwait Cross-sectional 1551 Kuwaiti adult subjects Smoking history Self-reported All 107/182 249/976 2.30 (1.75–3.04) Alqatahni et al [32] Saudi Arabia Cross-sectional 100 male participants with peri-implantitis Current smoking Self-reported All 20/15 11/21 2.55 (0.95–6.85) AlSadhan [7] Saudi Arabia Cross-sectional Male and female students Smoking history Self-reported All 66/173 468/1636 1.33 (0.99–1.80) Al-Zahrani et al [33] Saudi Arabia Cross-sectional 38 consecutive type 2 diabetic patients were recruited from among patients who presented for treatment at a University hospital Smoking history Self-reported All 3/7 13/15 0.49 (0.11–2.31) Ayo-Yusuf et al [34] South Africa Cross-sectional 896 patients examined between January and October 2004 were retrospectively analyzed. Current smoking Halimeter: No halitosis considered in subjects with halitosis measurement of 0–1 All 119/133 206/431 1.87 (1.39–2.52) Babazadeh et al [35] Iran ...…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Reference Country Study design Study participants Smoking definition Diagnosis of halitosis Subgroup (halitosis, YES/NO) Smokers Nonsmokers OR Patient group (n) (n) (95% CI) Al Ansari et al [31] Kuwait Cross-sectional 1551 Kuwaiti adult subjects Smoking history Self-reported All 107/182 249/976 2.30 (1.75–3.04) Alqatahni et al [32] Saudi Arabia Cross-sectional 100 male participants with peri-implantitis Current smoking Self-reported All 20/15 11/21 2.55 (0.95–6.85) AlSadhan [7] Saudi Arabia Cross-sectional Male and female students Smoking history Self-reported All 66/173 468/1636 1.33 (0.99–1.80) Al-Zahrani et al [33] Saudi Arabia Cross-sectional 38 consecutive type 2 diabetic patients were recruited from among patients who presented for treatment at a University hospital Smoking history Self-reported All 3/7 13/15 0.49 (0.11–2.31) Ayo-Yusuf et al [34] South Africa Cross-sectional 896 patients examined between January and October 2004 were retrospectively analyzed. Current smoking Halimeter: No halitosis considered in subjects with halitosis measurement of 0–1 All 119/133 206/431 1.87 (1.39–2.52) Babazadeh et al [35] Iran ...…”
Section: Resultsmentioning
confidence: 99%
“…The sensitivity analysis shown in Fig. 4 includes six studies [32] , [34] , [35] , [41] , [42] , as the studies by Rech et al [38] , Jiun et al [37] , and Romano et al [39] accounted for 20% of all interstudy heterogeneity. The results of this analysis also showed an increased risk of halitosis among current smokers in both fixed and random effects models (ORs = 1.43 [95% CI, 1.26–1.63] and OR = 1.49 [95% CI, 1.15–1.92], respectively; I 2 = 65%).…”
Section: Resultsmentioning
confidence: 99%